A high-entropy alloy material and a preparation method and application thereof
Patent Information
- Application Number
- CN202610947181.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-29
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]但是,申请人经深入研究后发现,上述技术制备的CoFe@NC氮掺杂碳基催化材料的OER催化活性显著不足(请参见附图9),无法同时满足可充电锌-空气电池对ORR/OER双功能催化的要求,难以实现高效稳定的充放电循环,限制了其在可充电锌-空气电池中的实际应用
[0016]本发明以FeCoNiCuAl五元高熵普鲁士蓝类似物(PBA)为金属源与结构前驱体,通过2,4-二羟基苯甲酸(DA)与六亚甲基四胺(HMT)在PBA表面原位水热包覆形成均匀有机聚合物层,有效抑制高温热解过程中金属颗粒团聚;再将包覆产物与双氰胺充分混合,于氮气惰性气氛下800℃高温煅烧碳化,最终制备得到氮掺杂碳层均匀封装的FeCoNiCuAl高熵合金催化材料。该材料兼具高比表面积多级孔结构与五元高熵合金多元金属协同效应,可高效调控氧还原反应(ORR)与氧析出反应(OER)中间体吸附-脱附行为,显著降低反应过电位、加快反应动力学,作为可充电锌-空气电池正极双功能电催化剂使用时,能够同时实现优异ORR与OER催化活性,并大幅提升电池充放电循环稳定性与使用寿命,有效解决现有双金属氮掺杂碳催化剂OER性能不足、双功能催化失衡的技术缺陷。
Smart Images

Figure CN122907654A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc-air battery electrocatalyst composite materials, specifically to high-entropy alloy cathode materials. Background Technology
[0002] With the continued growth of global energy demand, rechargeable zinc-air batteries, with their outstanding advantages such as high energy density, abundant raw materials, and environmental friendliness, have become a technology with great industrialization potential in the field of new energy storage. The charge-discharge cycle of zinc-air batteries relies on the combined completion of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at the positive electrode. However, the core bottleneck for their industrial application lies in the fact that both ORR and OER are multi-electron transfer reactions, exhibiting inherent defects such as complex reaction pathways, slow kinetics, high overpotential, and low exchange current density, which severely restrict the battery's energy conversion efficiency and charge-discharge performance. Currently, although commercially available precious metal catalysts such as Pt / C and IrO2 possess certain catalytic activity, they suffer from insufficient bifunctional catalysis, easy deactivation during long-term cycling, resource scarcity, and high cost, failing to meet the needs of large-scale applications of rechargeable zinc-air batteries. Therefore, the development of low-cost, high-activity, and high-stability non-precious metal bifunctional oxygen electrocatalysts is urgently needed.
[0003] Existing technology CN115149008B discloses a 3D nitrogen-doped carbon framework material for encapsulating alloys and its preparation method. This technology uses bimetallic CoFe-PBA as the metal source and template, in-situ introducing DA and HMT-derived polymer coating layers onto its surface, then mixing it with dicyandiamide and calcining it under an inert atmosphere to prepare a 3D porous network structure CoFe@NC nitrogen-doped carbon-based catalytic material. Performance test results show that this material has a high specific surface area, hierarchical porous structure, and high nitrogen doping content. In an alkaline system, it exhibits superior ORR onset potential, half-wave potential, and limiting current density compared to commercial 40% Pt / C materials, while also possessing excellent discharge stability and power density, making it suitable as a cathode ORR catalyst for zinc-air batteries.
[0004] However, after in-depth research, the applicant discovered that the OER catalytic activity of the CoFe@NC nitrogen-doped carbon-based catalytic material prepared by the above technology is significantly insufficient (see appendix). Figure 9 It cannot simultaneously meet the ORR / OER dual-function catalysis requirements of rechargeable zinc-air batteries, making it difficult to achieve efficient and stable charge-discharge cycles, thus limiting its practical application in rechargeable zinc-air batteries. Summary of the Invention
[0005] The purpose of this application is to provide a high-entropy alloy material with better ORR / OER bifunctional electrocatalytic effect, which is achieved through the following technical solution:
[0006] A method for preparing a high-entropy alloy material includes the following steps: S1, coordinating ferrocyanide ions with metal ions to prepare a FeCoNiCuAl-PBA precursor; the metal ions include divalent nickel ions, trivalent aluminum ions, divalent copper ions, and divalent cobalt ions; S2, mixing the FeCoNiCuAl-PBA precursor, 2,4-dihydroxybenzoic acid, and hexamethylenetetramine, and performing hydrothermal treatment to obtain FeCoNiCuAl-PBA@DA-HMT; S3, mixing the FeCoNiCuAl-PBA@DA-HMT with dicyandiamide, and performing pyrolysis carbonization under an inert atmosphere to obtain the high-entropy alloy material.
[0007] Preferably, in step S1, the molar ratio of divalent nickel ions, trivalent aluminum ions, divalent copper ions, divalent cobalt ions and ferrous ions is (3~5):(3~5):(5~7):(5~7):(7~9).
[0008] Preferably, step S1 further includes the following steps: dissolving a metal salt containing divalent nickel ions, trivalent aluminum ions, divalent copper ions and divalent cobalt ions and sodium citrate in water to obtain solution A; dissolving potassium ferrocyanide in water to obtain solution B; mixing solution A and solution B to carry out a coordination reaction, and obtaining the FeCoNiCuAl-PBA precursor after precipitation, washing and drying.
[0009] Preferably, in step S2, the mass ratio of the FeCoNiCuAl-PBA precursor, 2,4-dihydroxybenzoic acid and hexamethylenetetramine is 1:(4~5):(1~2).
[0010] Preferably, in step S2, the hydrothermal treatment conditions are 130~200℃ and 10~15h.
[0011] Preferably, in step S3, the mass ratio of FeCoNiCuAl-PBA@DA-HMT to dicyandiamide is 1:(18~25).
[0012] Preferably, in step S3, the pyrolysis carbonization conditions are 700~900℃ and the time is 2.5~4h.
[0013] A high-entropy alloy material is prepared using any of the preparation methods described above.
[0014] The above-mentioned high-entropy alloy material is used in zinc-air batteries.
[0015] Compared with the prior art, this application has the following beneficial effects:
[0016] This invention uses a pentagonal high-entropy Prussian blue analogue (PBA) of FeCoNiCuAl as the metal source and structural precursor. A uniform organic polymer layer is formed by in-situ hydrothermal coating of the PBA surface with 2,4-dihydroxybenzoic acid (DA) and hexamethylenetetramine (HMT), which effectively inhibits the agglomeration of metal particles during high-temperature pyrolysis. The coating product is then thoroughly mixed with dicyandiamide and calcined at 800°C under a nitrogen inert atmosphere to obtain a nitrogen-doped carbon layer uniformly encapsulated FeCoNiCuAl high-entropy alloy catalyst material. This material combines a high specific surface area hierarchical porous structure with the synergistic effect of five-element high-entropy alloy multi-metals, which can efficiently regulate the adsorption-desorption behavior of oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) intermediates, significantly reduce reaction overpotential, and accelerate reaction kinetics. When used as a bifunctional electrocatalyst for the cathode of rechargeable zinc-air batteries, it can simultaneously achieve excellent ORR and OER catalytic activities, and greatly improve the battery charge-discharge cycle stability and lifespan, effectively solving the technical defects of insufficient OER performance and bifunctional catalytic imbalance of existing bimetallic nitrogen-doped carbon catalysts. Attached Figure Description
[0017] The attached diagram will be briefly described below:
[0018] Figure 1 In the image, (ab) is a TEM image of the high-entropy alloy material FeCoNiCuAl@NC, (c) is a high-resolution transmission electron microscope image of the high-entropy alloy material FeCoNiCuAl@NC, and (dk) is a dark-field STEM image of the high-entropy alloy material FeCoNiCuAl@NC and the corresponding elemental mapping.
[0019] Figure 2 The XRD pattern of the high-entropy alloy material FeCoNiCuAl@NC;
[0020] Figure 3 In the figure, (a) is the N2 isothermal adsorption-desorption curve of the high-entropy alloy material FeCoNiCuAl@NC, and (b) is the pore size distribution curve of the high-entropy alloy material FeCoNiCuAl@NC.
[0021] Figure 4 In the figure, (a) is the full-spectrum XPS of the high-entropy alloy material FeCoNiCuAl@NC, (b) is the Fe 2p peak, (c) is the Co 2p peak, (d) is the Ni 2p peak, (e) is the Cu 2p peak, (f) is the Al 2p peak, and (g) is the N 1s peak.
[0022] Figure 5In the table, (a) shows the CV curve of the high-entropy alloy material FeCoNiCuAl@NC in 0.1MKOH saturated with Ar and O2; (b) shows the LSV curve of the ORR of the high-entropy alloy materials FeCoNiCuAl@NC, FeCoNi@NC, FeCoNiCu@NC and 40%Pt / C in 0.1MKOH saturated with Ar and O2 at a rotation speed of 2500 rpm.
[0023] Figure 6 In the figure, (a) is the LSV curve of the high-entropy alloy material FeCoNiCuAl@NC at 4000-6000 rpm, and the inset is its corresponding KL curve; (b) is the Tafel plot corresponding to the ORR LSV curve of different catalysts; (c) is the ORR hydrogen peroxide yield of different catalysts obtained from RRDE; and (d) is the ORR number of electrons transferred obtained from RRDE.
[0024] Figure 7 In the figure, (a) is the open-circuit voltage of high-entropy alloy materials FeCoNiCuAl@NC and Pt / C as a function of time, (b) is the discharge polarization curve and power density curve of zinc-air batteries with different alloy materials and Pt / C, (c) is the rate curve of high-entropy alloy material FeCoNiCuAl@NC, and (d) is the specific capacity of zinc-air batteries based on high-entropy alloy material FeCoNiCuAl@NC.
[0025] Figure 8 The constant current cycling stability diagram of the high-entropy alloy material FeCoNiCuAl@NC;
[0026] Figure 9 LSV curves of the OER of the high-entropy alloy material FeCoNiCuAl@NC in 0.1 MkOH electrolyte;
[0027] Figure 10 The background art cites patent CN115149008B, which describes the LSV curve of the OER of 3DCoFe@NC in 0.1M KOH electrolyte. Detailed Implementation
[0028] The present application will now be further described by way of specific embodiments. Those skilled in the art will be able to implement the present application based on these descriptions. Furthermore, the embodiments of the present application described below are generally only a part of the embodiments of the present application, and not all of the embodiments. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present application without inventive effort should fall within the scope of protection of the present application.
[0029] Example 1
[0030] A method for preparing a high-entropy alloy material FeCoNiCuAl@NC specifically includes the following steps:
[0031] (1) Synthesis of FeCoNiCuAl-PBA precursor
[0032] 4 mmol nickel nitrate hexahydrate, 4 mmol aluminum nitrate nonahydrate, 6 mmol copper nitrate trihydrate, 6 mmol cobalt nitrate hexahydrate, and 6.58 g sodium citrate were weighed and dissolved in 500 mL of deionized water. The mixture was stirred until homogeneous to obtain solution A. 8 mmol potassium ferrocyanide was weighed and dissolved in 200 mL of deionized water. The mixture was stirred until homogeneous to obtain solution B. Solutions A and B were stirred separately for 1 h. Solution B was then slowly poured into solution A while stirring continuously. The mixture was then allowed to precipitate at room temperature for 24 h. The resulting product was washed several times by centrifugation with ethanol and deionized water, and then dried in a vacuum drying oven at 60 °C for 24 h to obtain the FeCoNiCuAl-PBA precursor.
[0033] (2) Synthesis of FeCoNiCuAl-PBA@DA-HMT
[0034] 0.1534 g of the above FeCoNiCuAl-PBA precursor was added to 240 mL of deionized water and ultrasonically dispersed for 30 min, followed by stirring for 20 min to form a uniform dispersion. 0.74 g of 2,4-dihydroxybenzoic acid (DA) and 0.28 g of hexamethylenetetramine (HMT) were added to the dispersion, and stirring was continued for 30 min to obtain a uniform suspension. The suspension was transferred to a 100 mL hydrothermal reactor and hydrothermally reacted at 160 °C for 12 h. After cooling to room temperature, the mixture was washed with deionized water and ethanol, and vacuum dried at 60 °C for 24 h to obtain FeCoNiCuAl-PBA@DA-HMT.
[0035] (3) Preparation of high-entropy alloy material FeCoNiCuAl@NC
[0036] FeCoNiCuAl-PBA@DA-HMT and dicyandiamide were placed in a mortar at a mass ratio of 1:20 and thoroughly ground and mixed. The mixture was then transferred to a tube furnace and calcined at 800℃ for 3 hours under a nitrogen atmosphere. After natural cooling to room temperature, the high-entropy alloy material FeCoNiCuAl@NC was obtained.
[0037] Comparative Example 1
[0038] The preparation method of the high entropy alloy material in this comparative example is basically the same as that in Example 1, except that: in step (1), copper nitrate and aluminum nitrate are not added, and FeCoNi-PBA is prepared by using only three metal salts: Fe, Co and Ni; after being coated with DA-HMT and calcined, FeCoNi@NC is obtained.
[0039] Comparative Example 2
[0040] The preparation method of the high entropy alloy material in this comparative example is basically the same as that in Example 1, except that: aluminum nitrate is not added in step (1), and FeCoNiCu-PBA is prepared by using four metal salts: Fe, Co, Ni and Cu; after being coated with DA-HMT and calcined, FeCoNiCu@NC is obtained.
[0041] Comparative Example 3
[0042] This comparative example uses the method disclosed in the background art cited patent CN115149008B to prepare CoFe@NC alloy material. For specific preparation steps, please refer to Example 1 of the patent specification. Finally, CoFe@NC is obtained.
[0043] Performance Test 1
[0044] This performance test characterized the microstructure, crystal structure, pore structure, and surface elemental composition of the FeCoNiCuAl@NC catalytic material to confirm that the material's structure and composition meet the design expectations.
[0045] (1) Transmission electron microscopy (TEM / HRTEM / STEM-EDS) test
[0046] This performance test was conducted on FeCoNiCuAl@NC using transmission electron microscopy. The test method was as follows: a Tecnai G2 F30 S-Twin transmission electron microscope was used to observe the internal morphology, lattice fringes, and elemental distribution of the material. Please refer to [link to test results] for details. Figure 1 This indicates that FeCoNiCuAl@NC exhibits a uniform core-shell structure with a lattice spacing of 0.202 nm, corresponding to the (110) crystal plane of the Fe-based high-entropy alloy; the seven elements C, N, Fe, Co, Ni, Cu and Al are uniformly distributed, confirming that the pentagonal high-entropy alloy was successfully encapsulated by nitrogen-doped carbon.
[0047] (2) X-ray diffraction (XRD) test
[0048] X-ray diffraction was performed on FeCoNiCuAl@NC for this performance test. The test method was as follows: a Bruker D8 Advance diffractometer (Germany) was used with a Co target, the scanning range was 5~90°, and the scanning speed was 10°·min. -1 Please see the test results. Figure 2 The results indicate that the material exhibits a broad peak of amorphous carbon at 2θ = 20~30°, and characteristic peaks of BCC structure high-entropy alloys at 44°, 65°, and 82°, with no obvious impurity phases, confirming the successful synthesis of single-phase FeCoNiCuAl high-entropy alloy.
[0049] (3) Nitrogen isothermal adsorption-desorption (BET / BJH) test
[0050] This performance test examined the specific surface area and pore size distribution of FeCoNiCuAl@NC. The test method was as follows: a Micromeritics ASAP 2460 analyzer was used, and the sample was degassed at 200℃ for 8 hours. Calculations were performed using the BET and BJH models. Please refer to [link to relevant documentation] for the test results. Figure 3 This indicates that the material has a type IV isotherm, an H3 hysteresis loop, and a specific surface area as high as 440.10 m². 2 ·g -1 It has a microporous-mesoporous hierarchical pore structure, which can provide sufficient active sites and mass transfer channels for electrochemical reactions.
[0051] (4) X-ray photoelectron spectroscopy (XPS) test
[0052] This performance test examined the surface elemental valence states and bonding of FeCoNiCuAl@NC using a Thermo Scientific K-Alpha photoelectron spectroscopy system. The test results are available in [link to results]. Figure 4 This indicates that the material surface contains C, N, Fe, Co, Ni, Cu, and Al elements, with each metal element exhibiting its corresponding valence state. Nitrogen exists as a dopant, confirming that the material composition is consistent with the design.
[0053] Performance Test 2
[0054] This performance test evaluated the electrochemical performance of FeCoNiCuAl@NC and the control sample, including ORR, OER, zinc-air battery discharge, and cycle stability, to assess their catalytic and application performance.
[0055] (1) Cyclic Voltmeter (CV) Test
[0056] The performance of FeCoNiCuAl@NC was tested by cyclic voltammetry. The test method was as follows: three-electrode system, 0.1 M KOH electrolyte, Ar / O2 saturation, potential 0.1~1.1 V, scan rate 50 mV·s. -1 Please see the test results. Figure 5 (a) indicates that the material exhibits a significant ORR reduction peak in O2 saturated electrolyte and shows no response in Ar, confirming its intrinsic oxygen reduction catalytic activity.
[0057] (2) Linear scan voltammetry (ORR-LSV) test
[0058] This performance test performed ORR-LSV tests on FeCoNiCuAl@NC, FeCoNi@NC, FeCoNiCu@NC, and 40%Pt / C. The test method was as follows: three-electrode system, rotation speed 2500 rpm, scan rate 10 mV·s. -1 Please see the test results. Figure 5 (b) shows that the ORR onset potential, half-wave potential, and limiting current density of the pentagonal FeCoNiCuAl@NC are significantly better than those of the ternary and quaternary comparative samples and commercial Pt / C, confirming that the introduction of Al can repair the performance degradation caused by Cu and achieve high entropy synergistic enhancement.
[0059] (3) ORR kinetics (KL, Tafel, selectivity) test
[0060] This performance test performed speed-dependent LSV, Tafel, and RRDE selectivity tests on FeCoNiCuAl@NC and the control sample. The test method was as follows: LSV was tested at 4000~6000 rpm and the KL equation was calculated. Tafel curves were plotted from the LSV results, and H2O2 yield and electron transfer number were calculated from the RRDE results. Please refer to [link to test results]. Figure 6 This indicates that the ORR of FeCoNiCuAl@NC follows a 4-electron transfer path, with a low Tafel slope, rapid kinetics, and excellent selectivity.
[0061] (4) Linear sweep voltammetry of oxygen evolution reaction (OER)
[0062] This performance test performed OER-LSV testing on FeCoNiCuAl@NC. The test method was as follows: three-electrode system, 0.1 MkOH electrolyte, rotation speed 2500 rpm, potential 0.86~1.86 V, scan rate 10 mV·s. -1 Please see the test results. Figure 9 This indicates that FeCoNiCuAl@NC exhibits excellent oxygen evolution catalytic activity, with low overpotential and fast kinetics, demonstrating highly efficient OER catalytic capability.
[0063] (5) OER performance test of the comparison sample CoFe@NC
[0064] This performance test performed OER-LSV testing on the CoFe@NC nitrogen-doped carbon-based catalyst material in the background technology, using the same testing method as described above. Please refer to [link to test results]. Figure 10 This indicates that the OER catalytic activity of the bimetallic CoFe@NC is significantly weak, with high overpotential and insufficient performance, failing to meet the dual-functional catalytic requirements of rechargeable zinc-air batteries.
[0065] (6) Zinc-air battery assembly test
[0066] Preparation of the air electrode: A PTFE emulsion containing 15% (by weight) of the carbon paper was coated onto Toray carbon paper and dried. Then, a PTFE emulsion mixture containing 60 wt.% carbon black was coated onto the surface and dried again, yielding a carbon black loading of 1 mg·cm⁻¹. -2 An air diffusion layer was constructed. An air electrode was prepared by ultrasonically dispersing a mixture of FeCoNiCuAl@NC, Nafion solution, water, and ethanol, and then coating it onto the surface of the air diffusion layer. The loading amounts of FeCoNiCuAl@NC and 40% Pt / C on the air diffusion layer were both 1 mg·cm³. -2 .
[0067] The rechargeable zinc-air battery is assembled from a 0.5 mm zinc sheet, a 6 mol / L KOH electrolyte (containing 0.2 mol / L zinc acetate), an air electrode, and copper foil. The charge-discharge polarization curves were obtained by linear sweep voltammetry using a German Zahner electrochemical workstation, and the power density curve was calculated. The discharge voltage was set to 0.4–1.56 V, the charging voltage to 1.3–2.6 V, and the scan rate to 10 mV·s. -1 Using a blue electric system at 10 mA·cm -2 Constant current charge-discharge tests were conducted at a current density to observe its cycle stability. The cycle time was 5 min discharge / 5 min charge. The cycles were repeated until the zinc-air battery voltage showed a significant decay, and its constant current charge-discharge performance curve was obtained.
[0068] The primary zinc-air battery is assembled from a 0.5 mm zinc sheet, a 6 mol / L KOH electrolyte, an air electrode, and copper foil. The discharge polarization curves and power density curves are the same as those of the rechargeable zinc-air battery. The discharge stability of the battery was tested using a Zahner electrochemical workstation via chronopotentiometric method, with a controlled current density of 20 mA·cm⁻¹. -2 Record the potential changes during 100 hours of discharge to observe the battery life degradation.
[0069] The test results are shown in Figure 7. The FeCoNiCuAl@NC-based battery has a higher open-circuit voltage, greater power density, excellent rate performance and higher specific capacity, and outstanding battery application performance. The test results are shown in Figure 8. The charge and discharge voltage of this material does not decrease significantly during long-cycle cycling, and its structure and catalytic performance remain stable, which can meet the long-term use requirements of rechargeable zinc-air batteries.
Claims
1. A method for preparing a high-entropy alloy material, characterized in that, Includes the following steps: S1. A FeCoNiCuAl-PBA precursor is prepared by coordinating ferrocyanide ions with metal ions; the metal ions include divalent nickel ions, trivalent aluminum ions, divalent copper ions, and divalent cobalt ions. S2, FeCoNiCuAl-PBAl precursor, 2,4-dihydroxybenzoic acid and hexamethylenetetramine were mixed and subjected to hydrothermal treatment to obtain FeCoNiCuAl-PBAl@DA-HMT; S3. The FeCoNiCuAl-PBAl@DA-HMT is mixed with dicyandiamide and subjected to pyrolysis carbonization under an inert atmosphere to obtain a high-entropy alloy material.
2. The method for preparing a high-entropy alloy material according to claim 1, characterized in that, In step S1, the molar ratio of divalent nickel ions, trivalent aluminum ions, divalent copper ions, divalent cobalt ions and ferrous ions is (3~5):(3~5):(5~7):(5~7):(7~9).
3. The method for preparing a high-entropy alloy material according to claim 1, characterized in that, Step S1 further includes the following steps: dissolving a metal salt containing divalent nickel ions, trivalent aluminum ions, divalent copper ions and divalent cobalt ions and sodium citrate in water to prepare solution A; dissolving potassium ferrocyanide in water to prepare solution B; mixing solution A and solution B to carry out a coordination reaction, and obtaining the FeCoNiCuAl-PBA precursor after precipitation, washing and drying.
4. The method for preparing a high-entropy alloy material according to claim 1, characterized in that, In step S2, the mass ratio of the FeCoNiCuAl-PBA precursor, 2,4-dihydroxybenzoic acid and hexamethylenetetramine is 1:(4~5):(1~2).
5. The method for preparing a high-entropy alloy material according to claim 1, characterized in that, In step S2, the hydrothermal treatment conditions are 130~200℃ and 10~15h.
6. The method for preparing a high-entropy alloy material according to claim 1, characterized in that, In step S3, the mass ratio of FeCoNiCuAl-PBA@DA-HMT to dicyandiamide is 1:(18~25).
7. The method for preparing a high-entropy alloy material according to claim 1, characterized in that, In step S3, the pyrolysis carbonization conditions are 700~900℃ and the time is 2.5~4h.
8. A high-entropy alloy material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 7.
9. The application of the high-entropy alloy material according to claim 8 in a zinc-air battery.
Citation Information
Patent Citations
A 3D nitrogen-doped carbon skeleton material of a packaging alloy and a preparation method and application thereof
CN115149008B